Recent Advances in the Hardware Architecture of Flat Display Devices - Gökkaya, Utku (Izmir Institute of Technology, 2007)
Thesis will describe processing board hardware design for flat panel displays with integrated digital reception, the design challenges in flat panel displays with integrated digital reception explained with details. Thesis also includes brief explanation of flat panel technology and processing blocks. Explanations of building blocks of TV and flat panel displays are given before design stage for better understanding of design stage. Hardware design stage of processing board is investigated in two major steps, schematic design and layout design. First step of the schematic design is system level block diagram design. Schematic diagram is the detailed application level hardware design and layout is the implementation level of the design. System level, application level and implementation level hardware design of the TV processing board is described with details in thesis. Design challenges, considerations and solutions are defined in advance for flat panel displays.
Thesis (Master)--Izmir Institute of Technology, Electronics and Communication Engineering, Izmir, 2007
Includes bibliographical References (leaves: 115-117)
Text in English; Abstract: Turkish and English
xiii, 133 leaves
Keywords: TK7882.I6 G61 2007; Flat panel displays; Liquid crystal displays; Motherboards (Microcomputers)